Characterization of Micromegas with elongated pillars. (28th February 2017) - Sidiropoulou, O.; Gonzalez, B. Alvarez; Andreou, D.; Barak, L.; Bortfeldt, J.; Camerlingo, M.T.; Dubinin, F.; Farina, E.M.; Iengo, P.; Oliveri, E.; Samarati, J.; Sekhniaidze, G.; et al.
Abstract: We present a resistive Micromegas detector built with two different pillar shapes. The pillars are elongated and extend in the direction orthogonal to the readout strips. One region features pillars of 2 mm × 0.2 mm with 4.8 mm pitch while in the other region the pillars extend over the full width of the detector. The larger surface of the pillars allows for a better adhesion to the readout structure and a more uniform amplification gap. Results on the detector performance for the two regions are presented. No striking performance differences between the two regions were found.